2022
DOI: 10.1159/000525407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Direct Oral Anticoagulants’ Nonrecommended Dose in Atrial Fibrillation: A Meta-Analysis

Abstract: <b><i>Background:</i></b> The efficacy and safety profiles of nonrecommended direct oral anticoagulant (DOAC) doses in patients with nonvalvular atrial fibrillation (NVAF) are still undefined. <b><i>Summary:</i></b> We searched for randomized controlled trials and observational studies that compared nonrecommended versus recommended doses of DOACs, published up to December 2021. Primary study outcomes were ischemic stroke/transient ischemic attack/systemic emboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…A recent meta-analysis showed that patients treated with inappropriately lower DOAC doses do not have lower bleeding risk or higher AIS risk but have higher all-cause mortality [ 26 ]. Another meta-analysis showed increased risk of ischaemic events (including AIS) and mortality in patients on nonrecommended low DOAC doses without impact on major bleeding risk [ 29 ]. Another systematic review with meta-analysis did not find significantly higher risk of AIS, thromboembolism, bleeding, nor death in patients on off-label reduced DOAC doses [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that patients treated with inappropriately lower DOAC doses do not have lower bleeding risk or higher AIS risk but have higher all-cause mortality [ 26 ]. Another meta-analysis showed increased risk of ischaemic events (including AIS) and mortality in patients on nonrecommended low DOAC doses without impact on major bleeding risk [ 29 ]. Another systematic review with meta-analysis did not find significantly higher risk of AIS, thromboembolism, bleeding, nor death in patients on off-label reduced DOAC doses [ 30 ].…”
Section: Discussionmentioning
confidence: 99%